Hospitality and tourism service innovation: A bibliometric review and future research agenda. (April 2022) - Shin, Hakseung; Perdue, Richard R.
Abstract: Adopting a life cycle innovation process model, including innovation creation, diffusion, and evaluation, this research analyzed the knowledge development of service innovation research over the past decade with the goal of integrating the existing research and developing recommendations for future research. A co-citation analysis was conducted of 175 hospitality and tourism management innovation articles and 788 service management innovation articles collected from the ISI Web of Science. The results indicate the two literatures are quite disparate. Innovation performance and measurement were the foundational topics of the HTM research while the SM research focused more heavily on service-dominant logic (SDL) and dynamic capabilities. Regarding key topics which have evolved in the last decade, HTM research focused on collaborative innovation and knowledge sharing; the SM research emphasized open innovation and value co-creation. Bridging the two literatures, a conceptual model is proposed and opportunities for future hospitality service innovation research are proposed. Highlights: Hospitality and tourism (HTM) and service (SM) innovation research was analyzed. A life cycle innovation process model was adopted to examine service innovation research. The evolution of HTM innovation research was different from SM innovation research. Bridging the two literatures, a conceptual model is developed. An agenda for HTM research for innovation creation, diffusion, and evaluation is proposed.